Corrigendum to “Critical Review on Nanofluids: Preparation, Characterization, and Applications” - Mohamoud Jama (19691638) (2017)
Corrigendum to: Critical Review on Nanofluids: Preparation, Characterization, and Applications https://dx.doi.org/10.1155/2016/6717624, published online 26 October 2016. In the article titled “Critical Review on Nanofluids: Preparation, Characterization, and Applications” [1], reference [150] should be corrected as follows: [150] D. Gangacharyulu, Preparation and Characterization of Nanofluids and Some Investigation in Biological Applications, M.Tech. Thesis, Chemical Engineering, Thapar University, Patiala, India, 2010. Other Information Published in: Journal of Nanomaterials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2017/7830876